MATHEMATICAL LITERACY PROFILE OF GRADE VIII STUDENTS OF SMP PANGUDI LUHUR 1 YOGYAKARTA USING PENDIDIKAN MATEMATIKA REALISTIK INDONESIA APPROACH - Stephani Rangga Larasati; Veronika Fitri Rianasari (IJIET (International Journal of Indonesian Education and Teaching), 2017)
This research aims to investigate mathematical literacy of students grade VIII SMP Pangudi Luhur 1 Yogyakarta before and after learning using the Pendidikan Matematika Realistik Indonesia (PMRI) approach. This research was a descriptive qualitative research. The research subjects were 36 students of class VIII-F, SMP Pangudi Luhur 1 Yogyakarta. This research was conducted in March until July of 2016. The data was collected through observation, instructional video recording, and the results of pretest and posttest. Pretest and posttest was designed based on the characteristics of PISA (Program for International Student Assessment) problem. Instructional video was analyzed in qualitative with making a transcript of the video, determining topics of the data, and categorizing the data. The results of pretest and posttest were analyzed qualitatively to determine the students ability of mathematical literacy. The findings showed that before the implementation of PMRI the students get a better result in solving PISA problem level 2 compared with the result in solving PISA problem level 3, but after the implementation of PMRI the students get a better result in solving PISA problem level 3 compared with the result in solving PISA problem level 2. It is affected by PMRI learning which applied more focused to guide students to construct their mathematical knowledge instead of doing routine exercises of solving PISA problems.doi.org/10.24071/ijiet.2017.010106